Distributed Coordination of Fractional Dynamical Systems with Exogenous Disturbances. (20th July 2014) - Yang, Hongyong; Han, Fujun; Liu, Fei; Liu, Huixia; Zhao, Mei
Abstract : Distributed coordination of fractional multiagent systems with external disturbances is studied. The state observer of fractional dynamical system is presented, and an adaptive pinning controller is designed for a little part of agents in multiagent systems without disturbances. This adaptive pinning controller with the state observer can ensure multiple agents' states reaching an expected reference tracking. Based on disturbance observers, the controllers are composited with the pinning controller and the state observer. By applying the stability theory of fractional order dynamical systems, the distributed coordination of fractional multiagent systems with external disturbances can be reached asymptotically.